The experiences of informal care givers in home-based care in the ODI sub-district area in the North West Provice - LK Motswasele (AOSIS, 2008)
The purpose of this study was to explore and describe the experiences of informal caregivers in home-based care in the Odi Sub-District area in the Province of the North West.